Diagnostic accuracy of the waist-to-height ratio and other anthropometric indices for metabolically healthy obesity in the working population - Guzmán-García, José-Miguel; Romero-Saldaña, Manuel; Molina-Recio, Guillermo; Álvarez-Fernández, Carlos; Raya-Cano, Elena; Molina-Luque, Rafael (Frontiers in Nutrition, 2022)
Background: Approximately one-third of overweight individuals, and half of those with obesity, do not have cardiometabolic disorders. For this reason, a phenotype called metabolically healthy obese (MHO) has emerged to describe this population group. The early detection of this situation could save costs associated with the development of comorbidities or pharmacological interventions. Therefore, the aim is to know the prevalence of MHO in the working population and propose variables for its detection. Material and Methods: Cross-sectional descriptive study of 635 workers of the Cordoba City Council was carried out based on the results of the 2016 health surveillance. The outcome variables were the MHO, established based on the criteria of the IDF, NCEP - ATP III and Aguilar - Salinas. In addition, the degree of agreement between the different MHO criteria was studied using Cohen's kappa (k), and the predictive capacity of the anthropometric variables was assessed with Receiver Operator Curves. Results: The prevalence of MHO ranged from 6.6% to 9%. The highest agreement was reached between the IDF and NCEP-ATP III definitions (k = 0.811; 95%CI 0.724 - 0.898; p<0.001). The waist-to-height ratio (WHtR) showed the highest discriminant capacity for MHO, with its best cut-off point at 0.55 for all criteria used. Sensitivity ranged from 84% to 93%. Conclusion: The prevalence of MHO in the working population differed according to the criteria used for diagnosis. The anthropometric variable with the highest discriminant capacity for MHO was WHtR, presenting the same cut-off point in the three criteria analysed. Therefore, WHtR is the variable that best detects the presence of MHO.